Changes in lipid and fatty acid composition of late larval and puerulus stages of the spiny lobster (Panulirus cygnus) across the continental shelf of Western Australia - Phillips, Bruce; Jeffs, A.; Melville-Smith, R.; Chubb, C.; Nelson, M.; Nichols, P. (Elsevier, 2006)
The feeding of the late larval stages of the spiny lobster, Panulirus cygnus, and the energy reserves used by the non-feeding post-larvae for crossing the continental shelf of Western Australia were examined through their lipid composition. Lipid was a significant component of the biomass of all larval and post-larval samples (range 63 213 mg g 1 of dry biomass). The fatty acid profiles of late stage larvae (8-9) suggest that they were feeding on salps and small crustaceans, such as euphausids, from oligotrophic pelagic communities where herbivorous and microbial grazing is an important basis to the food web. There was a marked decrease in lipid content of post-larvae progressively across the continental shelf, and this corresponded closely with decreasing dry mass, suggesting that post-larvae were using lipid as an energy source during cross-shelf movement at a rate of 1.6 J km 1. This is considerably lower than for other spiny lobster species, suggesting that the post-larvae of the western rock lobster may use physical processes as well as active swimming for onshore transport. This may help to explain the large inter-annual variability in the post-larval settlement of this species, which is closely related to differences in weather patterns capable of greatly varying onshore advection processes.